Evaluation of LH, FSH, oestradiol, prolactin and tumour markers CEA and CA-125 in sera of Iraqi patients with endometrial cancer - Dawood Yasser Jassim; Mahdi Montadher Ali; Jumaa Azal Hamoody; Saad Rusul; Khadim Roaa M. (Scripta Medica, 2024)
Background/Aim: Endometrial cancer is one of the most prevalent gynaecologic cancers in advanced nations and act as the largest proportion of tumours occurring in the uterine corpus. The aim of the study was to identify potential diagnostic biomarkers for endometrial cancer among the evaluated hormones and tumour markers to enhance early detection and improve patient outcomes. Methods: A comparison was made between two groups of women: 30 individuals who were healthy and 30 individuals who had endometrial cancer. The participants in both groups were carefully selected to ensure that they were similar in terms of age and body mass index (BMI). Luteinising hormone (LH), follicle-stimulating hormone (FSH), oestradiol (E2), cancer antigen 125 (CA-125) and carcinoembryonic antigen (CEA) were analysed. Results: As compared to healthy individuals, females diagnosed with endometrial tumour and cancer exhibited notably elevated levels of LH, FSH, E2, CA-125 and CEA. Conversely, they demonstrated significantly reduced levels of prolactin in their serum. Conclusions: Endometrial cancer patients had significantly raised concentrations of LH, E2, FSH, PRL, CEA and CA-125 in their serum, indicating hormonal dysregulation in the development of endometrial cancer. It is not advisable to rely solely on LH, E2, FSH, PRL, CA-125 or CEA as screening markers for endometrial cancer. Instead, they should be considered as part of a comprehensive screening panel that needs to be developed in the future.